2017
DOI: 10.1002/2016jb013153
|View full text |Cite
|
Sign up to set email alerts
|

Low stress drops observed for aftershocks of the 2011 Mw 5.7 Prague, Oklahoma, earthquake

Abstract: In November 2011, three Mw ≥ 4.8 earthquakes and thousands of aftershocks occurred along the structurally complex Wilzetta fault system near Prague, Oklahoma. Previous studies suggest that wastewater injection induced a Mw 4.8 foreshock, which subsequently triggered a Mw 5.7 mainshock. We examine source properties of aftershocks with a standard Brune‐type spectral model and jointly solve for seismic moment (M0), corner frequency (f0), and kappa (κ) with an iterative Gauss‐Newton global downhill optimization me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 121 publications
(207 reference statements)
3
56
2
Order By: Relevance
“…The Milan event itself has a slightly lower estimated Δ σ (3.6 MPa) than would be expected by extrapolating the scaling trend of equation though still nearly an order of magnitude greater than the median value of the data set as a whole. The early aftershocks of Milan have lower than expected Δ σ values that appear to increase with time, consistent with observations of the Prague, OK, sequence (Sumy et al, ; Yenier et al, ). In early 2015, we observe another temporal cluster of high Δ σ events, with several other sequences later in 2015 and 2016 exhibiting analogous behavior.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The Milan event itself has a slightly lower estimated Δ σ (3.6 MPa) than would be expected by extrapolating the scaling trend of equation though still nearly an order of magnitude greater than the median value of the data set as a whole. The early aftershocks of Milan have lower than expected Δ σ values that appear to increase with time, consistent with observations of the Prague, OK, sequence (Sumy et al, ; Yenier et al, ). In early 2015, we observe another temporal cluster of high Δ σ events, with several other sequences later in 2015 and 2016 exhibiting analogous behavior.…”
Section: Resultsmentioning
confidence: 55%
“…Further, while the first‐order influence of injection on seismicity rate is apparent based on comparison to the historical record (Buchanan, ; Buchanan et al, ; Choy et al, ; Weingarten et al, ), its immediate influence on source properties is more nebulous both from an observational perspective due to the lack of historical precedent and from a geophysical perspective due to the complex, nonlinear interactions between anthropogenic stressing and the rupture dynamics of triggered events. Sumy et al () likewise observe both significant temporal changes in Δ σ and a lack of correlation with injection well distance for aftershocks of the 2011 Prague, Oklahoma sequence and attribute the low observed Δ σ values to the more widespread effects of regional injection patterns that weakened basement fault structures on regional rather than local length scales. Fluid injection on the spatial scale of that observed in southern Kansas during this time period may generate significant stress perturbations at distances of tens of kilometers or more through a combination of pore pressure increase and poroelastic stressing (Goebel et al, ; Segall & Lu, ).…”
Section: Discussionmentioning
confidence: 99%
“…This type of seismicity is generally of small moment magnitude ( M w < 3). However, some of these injection‐induced earthquakes have reached magnitudes greater than 5 (Ellsworth, ; Keranen et al, ; Petersen et al, ; Weingarten et al, ), such as the 2011 M w 5.6 Prague (Barnhart et al, ; Keranen et al, ; Norbeck & Horne, ; Sumy et al, ; Sun & Hartzell, ) or the September 2016 M w 5.8 Pawnee (Walter et al, ; Yeck et al, ) earthquakes in Oklahoma, USA.…”
Section: Introductionmentioning
confidence: 99%
“…The state of Oklahoma, in particular, has numerous moderate earthquakes, for example, the 2014 Cushing earthquakes (e.g., McNamara, Hayes, et al, ), the 2011 Prague earthquake (e.g., Keranen et al, ), and the 2016 Pawnee earthquake (Chen & Nakata, ). Some authors have suggested that induced seismicity has systematically lower stress drop and hence weaker ground motion than natural earthquakes (Hough, ; Sumy et al, ), while other studies (Huang et al, , ) have found that stress drops of induced earthquakes in the central USA are comparable to tectonic events in the same region. Instrumental intensities recorded for induced earthquakes at short distances are consistent with the predicted ground motions of tectonic earthquakes (Huang et al, ).…”
Section: Introductionmentioning
confidence: 99%